2012
DOI: 10.1038/nrurol.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in antenatal nonrefluxing hydronephrosis, megaureter and ureterocele

Abstract: Observation is a conservative management option in infants with nonrefluxing hydronephrosis, primary nonrefluxing megaureter and ureterocele diagnosed postnatally following antenatal detection of hydronephrosis. Antibiotic prophylaxis might be a sensible regimen under these circumstances to prevent UTI in this population who are potentially at increased risk. However, studies examining the efficacy of prophylactic antibiotics are sparse in this setting. For each condition, prophylactic policies seem extremely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
(116 reference statements)
1
12
0
1
Order By: Relevance
“…Our data showed that 63.2% of UTI occurred in the first 6 months of life confirming that this is the period at greatest risk, especially if they are males and affected by hydroureteronephrosis due to VUR, as suggested also by Castagnetti and colleagues 19. Frequency of VUR in our study was 5.4% of all patients with UTD, similar to that reported by Lee et al 20.…”
Section: Discussionsupporting
confidence: 91%
“…Our data showed that 63.2% of UTI occurred in the first 6 months of life confirming that this is the period at greatest risk, especially if they are males and affected by hydroureteronephrosis due to VUR, as suggested also by Castagnetti and colleagues 19. Frequency of VUR in our study was 5.4% of all patients with UTD, similar to that reported by Lee et al 20.…”
Section: Discussionsupporting
confidence: 91%
“…However, there are no convincing evidences that CAP can reduce the incidence of UTI in cases with UC after EI [24]. While further studies are necessary to clarify the effectiveness of CAP in this situation, it might be beneficial during critical period for symptomatic UTI demonstrated in the present study.…”
Section: Accepted Articlementioning
confidence: 61%
“…Antenatal hydronephrosis (AHN) is one of the most common anomalies detected on routine prenatal ultrasounds, affecting 1%-4.5% of all pregnancies [5]. It represents approximately 30% of all congenital defects detected on antenatal scans [6]. A variety of urological conditions can present with AHN, and differential diagnosis can usually be made only after thorough postnatal assessment [6].…”
Section: Introductionmentioning
confidence: 99%
“…It represents approximately 30% of all congenital defects detected on antenatal scans [6]. A variety of urological conditions can present with AHN, and differential diagnosis can usually be made only after thorough postnatal assessment [6]. The most common postnatal diagnoses include primary VUR in 10%-20% of cases, nonrefluxing HN (caused by ureteropelvic junction obstruction) in 10%-30% of cases, primary nonrefluxing megaureter in 5%-10% of cases, and ureterocele in 5% of cases [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation